1997
DOI: 10.3109/03005364000000027
|View full text |Cite
|
Sign up to set email alerts
|

Managing Tinnitus: A Comparison of Different Approaches to Tinnitus Management Training

Abstract: A series of studies examining the interaction between the characteristics of individual tinnitus sufferers and the effectiveness of the methods used to assist them has been conducted. The first of these studies provided a baseline description of 96 people with tinnitus, according to a range of audiological and psychological variables. In the present paper four differing tinnitus management programmes are described and the related changes in tinnitus perception reported three months after tinnitus management tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Some of these studies assessed tinnitus severity before treatment was initiated and assessed it again immediately after the treatment program was concluded [10-12]. Other studies included a follow-up assessment of tinnitus severity (usually in the form of a questionnaire) two weeks [13], four weeks [14], six weeks [15], three months [16] or six months [17] after the conclusion of a treatment program.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies assessed tinnitus severity before treatment was initiated and assessed it again immediately after the treatment program was concluded [10-12]. Other studies included a follow-up assessment of tinnitus severity (usually in the form of a questionnaire) two weeks [13], four weeks [14], six weeks [15], three months [16] or six months [17] after the conclusion of a treatment program.…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences regarding tinnitus have been observed in many studies (Dineen et al, 1997;Shargorodsky et al, 2010;Seydel et al, 2013). In some studies, the female patients reported a greater tinnitus annoyance than male patients and they perceived more stress than men did (Seydel et al, 2013).…”
Section: Epidemiologymentioning
confidence: 93%
“…Loud tinnitus or tinnitus sounds at a certain frequency could lead to increased distress, and patients who experience more complex sounds tend to report greater problems (Dineen et al, 1997). Another possible explanation for this result could be that preexisting psychological characteristics affect the way in which a patient reacts to tinnitus (Andersson et al, 2005).…”
Section: Hearing Impairmentmentioning
confidence: 99%
“…Others believe there is a less specific distracting or relaxing effect. Hallam et al [5] proposed that 'the emotion-engendering aspects of some external noises will influence tinnitus acceptability', while Dineen et al [6] found that patients using long-term white noise stimulation (during the day) reported improved coping ability but no change in tinnitus awareness. They proposed that long-term white noise stimulation may therefore be 'a behaviourally based coping strategy', or a way of gaining a sense of control over tinnitus.…”
Section: Introductionmentioning
confidence: 99%